Trends of the Romanian Cheese Market - Gabriel POPESCU; Nicolae ISTUDOR; Alina ZAHARIA (Communications of International Proceedings, 2020)
The food system should align to the principles of sustainable development by making the food more available, qualitative and locally made, with the least possible negative effects on the environment and the health of both humans and biodiversity. The main purpose of this investigation is to overview the trends of the Romanian cheese market between 2015 and 2019, while discussing it in terms of sustainability and by comparing the indicators internationally. A secondary data analysis was conducted based on several market indicator, like production, price, consumption, expenses and trade, collected from the Romanian Institute of Statistics, Eurostat and International Trade Centre. Some of the results indicate the need of developing the cheese market towards sustainability by promoting local consumption and production.
Keywords: Cheese; consumption; production; sustainable development.